Kinerja Bongkar Muat Barang di Pelabuhan Makassar dengan Menggunakan Crane Kapal PT. Pelni Cabang Makassar - Muhammad Awal Fajri; Fahri Ihsan; I Made Alet; Andi Hasmawati; M. Hamdy Meydiansyah (Hengkara Majaya, 2026)
This Cargo handling operations are one of the key elements in ensuring the smooth operation of a port, where speed, accuracy, and safety are important indicators for assessing service effectiveness. This study aims to analyze the effectiveness of cargo handling processes at Makassar Port carried out by PT. Pelni Makassar Branch using the ship’s crane as the main equipment. Common problems encountered in cargo handling include limited shore-based equipment, weather conditions, coordination among related parties, as well as technical and operational factors of the ship’s crane itself. The research method used is a descriptive qualitative approach, with data collected through direct field observations, interviews with operational staff, documentation, and literature studies. The data were analyzed by comparing the standard cargo handling time with the actual time achieved, as well as reviewing constraints and improvement measures taken. The results show that the use of the ship’s crane provides high flexibility in the cargo handling process, especially in conditions where port cargo handling equipment is limited or unavailable. However, the effectiveness of the ship’s crane is influenced by lifting capacity, technical condition of the equipment, operator experience, and cargo stowage arrangement inside the vessel. Observations indicate that the average cargo handling speed using the ship’s crane is slightly below the optimal standard due to waiting times and technical constraints, such as equipment maintenance, vessel positioning adjustments, and unfavorable weather conditions. Nevertheless, good coordination between the vessel’s crew, crane operators, and stevedores can minimize delays. This study recommends improving operator training, conducting regular equipment maintenance, optimizing cargo stowage planning, and integrating operational schedules between the port and vessels to enhance cargo handling effectiveness at Makassar Port.